USM-SCFE TECH AGREES TO COLLABORATE IN GREEN TECHNOLOGY FOR PHARMACEUTICAL INDUSTRY - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, September 2015 – Universiti Sains Malaysia (USM) through the School of Pharmaceutical Sciences (PPSF) recently signed a Collaboration Agreement with SCFE Tech Sdn. Bhd., a Malaysian subsidiary company of KCE Ltd. based in Japan that specialises in the manufacturing and extraction of biochemical products for health supplements, food additives and cosmetic industries.